The relationship between organizational justice and organizational citizenship behavior in staff of Allameh Tabatabai University - علی دلاور; مریم محمد تقی نسب (Allameh Tabataba'i University Press, 2015)
Objective: This study has been performed to investigate the relationship of organizational justice and organizational citizenship behavior staff Allameh Tabatabai University Methods: The sample consisted of 200 employees of Allameh Tabatabai University who were selected by random sampling method. Data collected by using two questionnaires of organizational justice and organizational citizenship behavior Toure Niehoff. For data analysis using Pearson correlation, multiple regression, structural equation, ANOVA and independent t-test. Data analyzed by SPSS-20 and LISREL-8/7 softwares. Results: results indicated that there is a significant relationship between organizational justice and organizational citizenship behavior, loyalty, cooperation and sportsmanship (p≤0/001) and conscientiousness (p≤0/05). indicators fit proposed model were good and Standardized regression coefficient of organizational justice on organizational citizenship behavior was 0/30. Of the dimensions of organizational justice, distributive justice and procedural were able to predict the organizational citizenship behavior (p≤0/05). By comparing the variables of organizational justice and organizational citizenship behavior at different levels of demographic variables, there was no significant difference. Conclusion: The present study confirms the impact of organizational justice on OCB employees. Therefore, by adopting strategies to increase organizational justice, can be taken effective steps in order to achieve the noble objectives of the organization.